Transformational Leadership Beyond Behavior: A Structural Equation Model of Motivation and Culture as Mediators of Teacher Effectiveness - Usman, Asep Tutun; Anisah, Ani Siti; Nazib, Fiqra Muhammad (Indonesian Scientific Publication, 2025)
Transformational leadership (TL) has become an important approach to improving teacher performance in various educational settings. In Indonesia’s secondary education sector, where leadership reforms are accelerating, it is essential to understand how TL influences teacher outcomes. This study examines the mediating roles of teacher motivation and organizational culture in the TL–performance relationship, using data from 300 teachers across SMP, SMA, SMK, and MA schools nationwide. This study applied a cross-sectional design and structural equation modeling (SEM) with bootstrapped mediation analysis to test direct and indirect pathways. The instruments used were the Indonesian version of MLQ 5X Short, adapted scales for motivation and culture, and the national PKG rubric for teacher performance. Confirmatory Factor Analysis (CFA) validated all constructs with strong fit indices (CFI > 0.91; RMSEA < 0.06). The results show that TL significantly predicts motivation (β = 0.61) and organizational culture (β = 0.53). Both variables strongly influence teacher performance (β = 0.47 and β = 0.42). The direct effect of TL on performance is modest (β = 0.18), which indicates that psychological and cultural mediators play a dominant role. The total explained variance in performance (R² = 0.51) confirms the importance of these indirect mechanisms. This study contributes to educational leadership theory by validating a dual mediation model in a developing country context, while offering practical insights for leadership training programs and policy reforms. It underscores the importance of building school cultures and enhancing intrinsic motivation to maximize leadership impact. Limitations include the cross sectional design, suggesting future research adopt longitudinal or mixed method approaches.